Design of a quadrature surface coil for hyperpolarized 13C MRS cardiac metabolism studies in pigs. Issue 2 (24th April 2013) - Giovannetti, G.; Frijia, F.; Hartwig, V.; Attanasio, S.; Menichetti, L.; Vanello, N.; Positano, V.; Ardenkjaer‐Larsen, J.H.; Lionetti, V.; Aquaro, G.D.; Marchi, D. De; Schulte, R.F.; et al.
ABSTRACT: This work describes the design of a quadrature surface coil constituted by a circular loop and a butterfly coil, employed in transmit/receive (TX/RX) mode for hyperpolarized 13 C studies of pig heart with a clinical 3T scanner. The coil characterization is performed by developing an SNR model for coil performance evaluation in terms of coil resistance, sample‐induced resistance and magnetic field pattern. Experimental SNR‐vs.‐depth profiles, extracted from the [1–13C]acetate phantom chemical shift image (CSI), showed good agreement with the theoretical SNR‐vs.‐depth profiles. Moreover, the performance of the quadrature coil was compared with the single TX/RX circular and TX/RX butterfly coil, in order to verify the advantage of the proposed configuration over the single coils throughout the volume of interest for cardiac imaging in pig. Finally, the quadrature surface coil was tested by acquiring metabolic maps with hyperpolarized [1–13C]pyruvate injected i.v. in a pig. © 2013 Wiley Periodicals, Inc. Concepts Magn Reson Part B (Magn Reson Engineering) 43B: 69–77, 2013